2017
DOI: 10.1093/ofid/ofx163.787
|View full text |Cite
|
Sign up to set email alerts
|

Early ID Outpatient Follow-up of OPAT Patients Reduces 30-day Readmission

Abstract: BackgroundAlthough weekly outpatient follow-up for patients discharged on outpatient parenteral antimicrobial therapy (OPAT) has been recommended, few practitioners follow this recommendation. No studies have examined the relationship between outpatient follow-up and patient outcomes for this population. We examined the association between outpatient ID follow-up and the risk for 30-day readmission for patients discharged on OPAT.MethodsWe conducted a retrospective cohort study using EMR data comprising 1102 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…We were most interested in determining whether implementation of the ID physician-led OPAT clinic led to appreciable differences in health outcomes. ID supervision of OPAT is routinely recommended by published guidelines, and several recent studies have demonstrated the importance of ID involvement in reducing readmissions and health care costs (2,3,16,17). In our study, although we found no significant change in 60-day readmission rate, there was a trend toward reduced ED use and readmissions.…”
Section: Discussioncontrasting
confidence: 55%
“…We were most interested in determining whether implementation of the ID physician-led OPAT clinic led to appreciable differences in health outcomes. ID supervision of OPAT is routinely recommended by published guidelines, and several recent studies have demonstrated the importance of ID involvement in reducing readmissions and health care costs (2,3,16,17). In our study, although we found no significant change in 60-day readmission rate, there was a trend toward reduced ED use and readmissions.…”
Section: Discussioncontrasting
confidence: 55%
“…Palms et al developed a 30-day admission predictive model for patients discharged to OPAT and found that follow-up at a clinic specialising in infectious diseases was a preventive factor for hospital admission [23]. Saini et al demonstrated that evaluation by an infectious diseases specialist within the first 14 days after enrolment in an OPAT program is associated with a lower risk of hospital admission within the first 30 days after discharge [24]. To our knowledge, there have been no studies establishing a direct relationship between post-enrolment evaluation and mortality.…”
Section: Plos Onementioning
confidence: 99%
“…2 In some jurisdictions, CPS may become involved with a high-conflict family when one or both parents report that the other parent (or a new partner) is abusing or neglecting the child or that drug or alcohol abuse or mental health issues are compromising the caring capacity of the other parent. 3 Custodial and noncustodial parents are the primary referral source for allegations in the context of child custody disputes. 4 CPS may also become involved because of risk of harm to the children due to exposure to high levels of conflict.…”
Section: Cps Involvement In High-conflict Separationsmentioning
confidence: 99%